Policentricity og the modern world and "non-WESTERN modernity" (Journal of Philosophy Culture and Political Science, 2023)
The modern world is faced with deep and interconnected challenges and crises that are becoming ever larger and more serious. The architecture of peace and security is under enormous pressure, which makes it urgent to manage global risks and build a sustainable future.In the modern globalized and interconnected world, not a single center of gravity can exist without interaction with other centers, without the interpenetration of economies, cultures, ideas, which necessitates mutual understanding and mutual respect. It is especially important to understand the fundamental plurality of development paths of the world, societies, cultures, identities, and their irreducibility to a single scenario - be it the Western or the Eastern path.In the context of the theory of cultural turns, attention should be paid to the following analytical categories that reveal the polycentrism of the modern world: “non-Western modernity”, “Asia as a method”, “Asian discourse about Asia”.All this raises questions of methodological self-renewal and cultural and civilizational self-awareness for modern cultural sciences. The importance of rejecting the rigorism of Eurocentrism, the need to understand the equivalence, equal status, equivalence of Eastern and Western thought and scientific traditions, their equal importance for each other are realized. The inclusion of the Eastern philosophical and cultural tradition in the broad context of global research will make it possible to understand the true meaning of the concepts of “world history”, “world philosophy”, “world culture”, and to formulate a new scientific picture of the world of the 21st century, which should be based on an understanding of its objective polycentricity.Key words: «cultural turns», polycentricity, "non-Western modernity".